Authority and the sacred aspects of the Christianisation of the Roman world - Brown, Peter 1935- (Cambridge Cambridge University Press, 1992)
The Christianisation of the Roman world lies at the root of modern Europe, yet at the time it was a tentative and piecemeal process. Peter Brown's fascinating study examines the factors which proved decisive and the compromises which made the emergence of the Christian 'thought world' possible: how the the old gods of the Roman Empire could be reinterpreted as symbols to further the message of the Church. Peter Brown also shows how Christian holy men were less representative of a triumphant faith than negotiators of a working compromise between the new faith and traditional ways of dealing with the supernatural worlds.
Preface -- 1. Christianisation : narratives and processes -- 2. The limits of intolerance -- 3. Arbiters of the holy : the Christian holy man in late antiquity -- Notes -- Index
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Church history, Primitive and early church, ca. 30-600; Church History -- Primitive and early church, ca. 30-600; Church history ; Primitive and early church, ca. 30-600; Rome ; Religion; Rome -- Religion; Rome -- Religion